Serum Level of Complement C1q is Associated with Contrast-Associated Acute Kidney Injury in Patients Undergoing Emergency Percutaneous Coronary Intervention - Tao J; Ye C; Dai W; Li D; Zhou M; Li Y (Dove Medical Press, 2021)
Jun Tao,1,* Chenglin Ye,2,* Wen Dai,1 Di Li,1 Man Zhou,1 Yan Li1 1Department of Clinical Laboratory, Renmin Hospital of Wuhan University, Wuhan, People's Republic of China; 2Department of Urology, Renmin Hospital of Wuhan University, Wuhan, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan Li; Wen Dai Tel +8613886079252; +8613476029919Email yanlitf1120@163.com; 527638620@qq.comBackground: As an inflammatory factor, complement C1q is related to the prevalence and progression of atherosclerosis; however, in patients undergoing emergency percutaneous coronary intervention (PCI), it is unclear whether C1q is related to the prevalence of contrast-associated acute kidney injury (CA-AKI).Methods: From November 2018 to March 2021, 1182 patients who underwent emergency PCI were continuously recruited. Patients were divided into CA-AKI group (n = 234) and non-CA-AKI group (n = 948). CA-AKI was defined as an increase in serum creatinine from the baseline level (≥ 25% or ≥ 0.5 mg/dL) 48- 72 hours after contrast exposure. All subjects were tested for serum C1q levels when they were admitted to the hospital.Results: Among the 1182 patients undergoing emergency PCI, 234 patients (19.80%) developed CA-AKI. The level of preoperative serum complement C1q in the CA-AKI group was significantly higher than that in the non-CA-AKI group. Logistic regression and restricted cubic spline analyses showed that the incidence of CA-AKI was positively associated with the serum C1q level pre-PCI. Univariate and multivariate logistic regression analyses showed that C1q was an independent predictor of whether CA-AKI occurred after emergency PCI. The area under the curve (AUC) of the C1q was 0.703 [95% confidence interval (CI) 0.667- 0.739] in patients receiving emergency PCI. CA-AKI model included the following three predictors: C1q, eGFR, and IABP use. The AUC of forecast probability was 0.718 [95% CI 0.682- 0.754].Conclusion: In patients receiving emergency PCI procedure, a high C1q level before PCI is associated with the increased risk of CA-AKI.Keywords: complement C1q, contrast-associated acute kidney injury, percutaneous coronary intervention, coronary heart disease, inflammation